Implementasi Pembelajaran PJOK di Masa Pandemi Covid-19 pada SMP Negeri Se-Kecamatan Tonjong Kabupaten Brebes - Alfrid Adarda Qutni; Martin Sudarmono (Universitas Negeri Semarang, 2022)
The Covid-19 phenomenon has forced PJOK learning activities to be carried out online. This study aims to find out how the implementation of PJOK learning during the COVID-19 pandemic at State Junior High Schools in Tonjong District, Brebes Regency. This study uses a qualitative method. Data collection techniques through observation, interviews, and documentation. The object of the research is a public junior high school in the District of Tonjong. The results showed that learning plans such as silabus and RPP were sourced from the MGMP, while teaching materials and assessment instruments had their own guidelines for each school. The method used is online. The media used is Whatsapp. The implementation of learning is not in accordance with the existing RPP. Learning evaluation is carried out on all aspects including affective aspects through observation, cognitive aspects through quizzes, and psychomotor aspects through practice videos. From the results of the study it can be concluded that in the aspect of learning planning it has been implemented well. In the aspect of implementing learning, teachers have not utilized the current technology, such as zoom or google meet. In the evaluation aspect, all aspects of the assessment have been carried out. One of the obstacles in PJOK learning activities is the limited quota and network, and there are some students who do not have mobile phones.